Stress and Burnout Among Finnish Dairy Farmers. Issue 3 (2nd July 2016) - Kallioniemi, Marja K.; Simola, Ahti; Kaseva, Janne; Kymäläinen, Hanna-Riitta
ABSTRACT: Psychosocial risks among farmers have increasingly been examined because of the ongoing changes in agriculture, such as restructuring of the industry, transition from family farming towards entrepreneurship, and climate change. The aims of the study were to determine the stressors, prevalence of stress and burnout, and variables associated with these symptoms among Finnish dairy farmers. In total 265 respondents completed a postal survey; their average age was 48 years, 44% were females and 56% males. The farms of the survey sample were larger (54 field hectares, 29 cows) than an average farm in Finland (37 hectares, 24 cows) in 2010. The most common stressors were external, such as "agricultural policy of the EU" (European Union) and "the treatment of farmers in society and the media." In addition, common stressors were related to farm and work, e.g., "amount of work, " unpredictability, and "animal diseases." The prevalence of stress (42%) was found to have increased compared with earlier studies and was greater than among the general working population. All respondents as a group were classified as having slight symptoms of burnout, and one tenth (9%) of dairy farmers had experienced severe burnout. Stressors related to the workload and health were associated with stress and burnout symptoms. Also, a poor economic situation and loneliness were related to stress. Burnout correlated with a tie stall barn type and with a farm not being involved in the milk production record system. Factors protecting against burnout included positive features of the work and living environment. The study revealed changes during the past decade and new features of the well-being at work on dairy farms in Finland.